Allele‐specific transcriptional activity of the variable number of tandem repeats of the inducible nitric oxide synthase gene is associated with idiopathic achalasia. Issue 2 (1st March 2017) - Sarnelli, Giovanni; Grosso, Michela; Palumbo, Ilaria; Pesce, Marcella; D'Alessandro, Alessandra; Zaninotto, Giovanni; Annese, Vito; Petruzzelli, Raffaella; Izzo, Paola; Sepulveres, Rossana; Bruzzese, Dario; Esposito, Giuseppe; et al.
Abstract : Background: Polymorphisms of genes involved in the regulation of the immune response are risk factors for achalasia, but their contribution to disease pathogenesis is unknown. Nitric oxide is involved both in immune function and inhibitory neurotransmission. Objective: The objective of this article is to assess the association and the functional relevance of the CCTTT‐inducible nitric oxide synthase ( NOS2 ) gene promoter polymorphism in achalasia. Methods: Genomic DNA was isolated from 181 achalasia patients and 220 controls. Genotyping of the (CCTTT)n repeats was performed by PCR and capillary electrophoresis, and data analyzed by considering the frequency of the different alleles. HT29 cells were transfected with iNOS luciferase promoter‐reporter plasmids containing different (CCTTT)n. Results: The alleles' distribution ranged from 7 to 18, with a peak frequency at 12 repeats. Analysis of the allele frequencies revealed that individuals carrying 10 and 13 CCTTT repeats were respectively less and more frequent in achalasia (OR 0.5, 95% CI 0.3–0.5 and OR 1.6, 95% CI 1–2.4, all p < 0.05). Long repeats were also significantly associated with an earlier onset of the disease (OR 1.69, 95% CI 1.13–2.53, p = 0.01). Transfection experiments revealed a similar allele‐specific iNOS transcriptional activity. Conclusion: The functional polymorphism (CCTTT) of NOS2 promoter is associated with achalasia, likely by an allele‐specific modulation of nitric oxide production.